The Place of Measurement and Evaluation in National Policy of Education in Nigeria Educational System (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This study examined the place of measurement and evaluation in the National Policy on Education in Nigeria’s educational system. The study was guided by three research questions and three hypotheses. A descriptive survey research design was adopted. The population of the study consisted of 5,420 educational stakeholders, while a sample of 542 respondents was selected using a 10% sampling technique. Data were collected using a structured questionnaire titled Measurement and Evaluation in National Policy on Education Questionnaire (MENPEQ). The instrument was validated by experts and tested for reliability using Cronbach Alpha, which yielded a coefficient of 0.82. Data collected were analyzed using mean and standard deviation to answer research questions, while z-test statistics were used to test the hypotheses at 0.05 level of significance. Findings of the study revealed that measurement and evaluation play a significant role in ensuring quality assurance in Nigerian education. It was also found that measurement and evaluation significantly influence curriculum implementation in schools. Furthermore, the study revealed that effective measurement and evaluation improve educational outcomes when properly implemented. However, several challenges such as inadequate teacher training, poor funding, large class sizes, and lack of assessment materials were found to hinder effective implementation of measurement and evaluation in Nigeria’s educational system. The hypotheses tested showed that measurement and evaluation have a significant effect on quality assurance, curriculum implementation, and educational outcomes. The study concluded that measurement and evaluation are essential components of the National Policy on Education and are critical for improving educational quality and accountability in Nigeria. It was recommended that government should strengthen teacher training, improve funding, and enhance the use of modern assessment tools to improve evaluation practices in schools.